Case report: New is not always better: treatment of non-bacterial thrombotic endocarditis - Akiki, Elias; Ahmad, Ali; El-Am, Edward A.; Casanegra, Ana I.; Klarich, Kyle W.; Kurmann, Reto (Frontiers in Cardiovascular Medicine, 2023)
An elderly female with metastatic adenocarcinoma of the lung and atrial fibrillation presented with multiple embolic strokes while on anticoagulation with Apixaban. After further investigation, a TEE showed lesions of non-bacterial thrombotic endocarditis on the mitral valve. A decision to switch the patient to LMWH for anticoagulation was then made and a follow-up TEE showed resolution of the NBTE. In this abstract, we show that heparin should remain as the anticoagulation agent of choice in the setting of NBTE associated with malignancy.